The effects of Cr and Si additions and deposition conditions on the structure and properties of the (Zr-Ti-Nb)N coatings. Issue 1 (January 2017) - Pogrebnjak, A.D.; Bagdasaryan, A.A.; Beresnev, V.M.; Nyemchenko, U.S.; Ivashchenko, V.I.; Kravchenko, Ya.O.; Shaimardanov, ZH.K.; Plotnikov, S.V.; Maksakova, O.
Abstract: In this study, (Zr-Ti-Nb)N, (Zr-Ti-Cr-Nb)N and (Zr-Ti-Cr-Nb-Si)N nitride coatings were obtained using a well-developed vacuum arc deposition. The systematical investigations demonstrate that the chemical composition, microstructure, and properties of the coatings intimately rely on the deposition parameters (pressure of working gas and substrate bias). Effects of Cr and Si additions on microstructure and mechanical properties of the (Zr-Ti-Nb)N coatings have been investigated using scanning electron microscopy (SEM) equipped with energy dispersive spectrum (EDS), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), transmission electron microscope (TEM), hardness measurements and adhesion testing. First-principles band-structure calculations and Gibbs-Rosenbaum triangle representation have been used to investigate the elemental and phase compositions in nitride coatings. The multi-component (Zr-Ti-Cr-Nb-Si)N and (Zr-Ti-Nb)N coatings are found to be a simple face-centered cubic (FCC) solid solution. For the coatings without Si, the structure is mainly composed of TiN fcc phase and Cr2 N trigonal modification. The hardness values were in the ranges (24–42 GPa). The (Zr-Ti-Nb)N, (Zr-Ti-Cr-Nb)N coatings provided the best adhesive strength in different conditions. The (Zr-Ti-Cr-Nb-Si)N coatings exhibited the worst adhesive strength, which may be attributed to the relative low hardness. Highlights: (Zr-Ti-Nb)N, (Zr-Ti-Nb-Cr)N and (Zr-Ti-Nb-Cr-Si)N coatings produced by vacuum arc deposition. The microstructure and mechanical properties of the coatings by using the different deposition parameters were examined. We discuss the effects of Cr and Si elements on the microstructure and properties of the (Zr-Ti-Nb)N coatings. First-principles band-structure calculations are carried out for describing the formation and structure of nitride coatings.